Cinema as an Educational Tool in Second Chance Schools: Opportunities and Challenges - Damala, Paraskevi (Adult Education Critical Issues, 2025)
This study examines the use of cinema as an educational tool in Second Chance Schools (SCS), focusing on the opportunities and challenges accompanying its integration into adult education. SCS provide adult learners with the chance to acquire fundamental knowledge and skills, addressing social and educational inequalities. Cinema, through its combined visual and auditory experience, offers an innovative teaching approach, enhancing emotional engagement, the understanding of complex concepts, and critical thinking. The main benefits of using cinema include the creation of an engaging learning environment, the development of collaboration and communication skills, and the strengthening of students’ emotional and cognitive connection to educational content. Simultaneously, pedagogical theories such as experiential learning (Kolb), social interaction (Vygotsky), and critical pedagogy (Freire) emphasize the importance of experiential learning through cinematic analysis. However, integrating cinema into SCS faces challenges, such as limited access to appropriate equipment and resources, resistance to change from educators and learners, and a lack of educational materials tailored to students' needs. Nonetheless, strategies are proposed, such as the careful selection of films, the design of activities that foster participation, and the creation of short cinematic projects by students, to enhance the approach's effectiveness. Overall, the use of cinema in SCS is a promising tool for improving the learning experience, fostering students’ personal development, and creating a more participatory and socially sensitive educational environment.